Poplar miR472a targeting NBS-LRRs is involved in effective defence against the necrotrophic fungus Cytospora chrysosperma. (17th August 2018) - Su, Yanyan; Li, Hui-Guang; Wang, Yonglin; Li, Shuang; Wang, Hou-Ling; Yu, Lu; He, Fang; Yang, Yanli; Feng, Cong-Hua; Shuai, Peng; Liu, Chao; Yin, Weilun; et al.
Abstract : ptc-miR472a-overexpressing poplar exhibited resistance to Cytospora chrysosperma and susceptibility to Colletotrichum gloeosporioides, while silenced lines exhibited the opposite phenotype, identifying a new strategy to improve plant disease resistance. Abstract: The hemibiotroph Colletotrichum gloeosporioides and the necrotroph Cytospora chrysosperma cause poplar foliage and stem disease, respectively, resulting in substantial economic losses. In this study, Populus trichocarpa ptc-miR472a was down-regulated in leaves treated with salicylic acid, jasmonic acid (JA) or bacterial flagellin (flg22). Here, ptc-miR472a and a short tandem target mimic (STTM) of miR472a were overexpressed in P. alba × P. glandulosa, and overexpression lines of miR472a and silenced lines of STTM472a were generated. Compared with the STTM472a and wild type lines, lower reactive oxygen species accumulation was detected in miR472a overexpressing plants treated with flg22, C. gloeosporioides or C. chrysosperma . In addition, the miR472a overexpressing lines exhibited the highest susceptibility to the hemibiotroph, C. gloeosporioides, but the highest effective defence response to the necrotroph, C. chrysosperma . The JA/ethylene marker gene ERF1 was rapidly up-regulated in miR472a overexpressing plants. Furthermore, five phased, secondary, small interfering RNAs (phasiRNAs) were confirmed in the miR472a overexpressing and STTM472a lines, triggering phasiRNAs predicted to enhance NBS-LRR silencing. Taken together, our results revealed that ptc-miR472a exerts a key role in plant immunity to C. gloeosporioides and C. chrysosperma by targeting NBS-LRR transcripts. This study provides a new strategy and method in plant breeding to improve plant disease resistance.